The Role of the Principal as a Manager in Improving the Quality of Education through Sociocultural Strengthening - Herawati, Lilik; Nurkolis, Nurkolis; Aryanto, Lilik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to explain the role of school principals as managers in improving the quality of education through sociocultural strengthening. A qualitative approach with a single-case study design was used to explore the managerial practices of school principals in planning, organizing, implementing, and supervising local culture-based programs, such as the Barongsai extracurricular program and the Adiwiyata program. Data were collected through semi-structured interviews, participatory observations, and documentation studies, and then analyzed using data reduction techniques, data presentation, and conclusion drawing, with validation through the triangulation of methods and sources. The results showed that school principals carried out managerial functions adaptively and collaboratively by involving local communities, developing programs based on the identification of environmental potential, dividing tasks based on teachers' competencies and interests, and implementing evidence-based supervision and reflective evaluation. This research presents implications related to the importance of contextual and value-oriented local cultural managerial leadership as a sustainable strategy in improving the quality of basic education, especially in multicultural environments.